Ответ: D) (4; 5); ( -4; -5)
Объяснение:
{х²+ху=36
{ху+у²=45
Сложим оба уравнения
х²+ 2ху + у² = 36 + 45
( х + у)² = 81
(х + у) = 9
(х + у) = - 9
х = 9 -у
Подставим в первое уравнение х = 9 - у
( 9 - у)² + у(9 - у) = 36
(9 - у) * 9 = 36
9 - у = 36 : 9
9- у = 4
у = 9 - 4
у = 5
х = 4
Подставим в первое уравнение х = -9 -у
(- 9 - у)² + у(-9 - у) = 36
(-9 - у) *(- 9) = 36
-9 - у = 36 : (-9)
-9 - у = -4
у = - 9 + 4
у = - 5
х = - 4
Ответ: (4; 5); ( -4; -5)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ: D) (4; 5); ( -4; -5)
Объяснение:
{х²+ху=36
{ху+у²=45
Сложим оба уравнения
х²+ 2ху + у² = 36 + 45
( х + у)² = 81
(х + у) = 9
(х + у) = - 9
х = 9 -у
Подставим в первое уравнение х = 9 - у
( 9 - у)² + у(9 - у) = 36
(9 - у) * 9 = 36
9 - у = 36 : 9
9- у = 4
у = 9 - 4
у = 5
х = 4
Подставим в первое уравнение х = -9 -у
(- 9 - у)² + у(-9 - у) = 36
(-9 - у) *(- 9) = 36
-9 - у = 36 : (-9)
-9 - у = -4
у = - 9 + 4
у = - 5
х = - 4
Ответ: (4; 5); ( -4; -5)